Wine sellin in the province of Leon in the eighteenth Century: types and problems - Juan M. BARTOLOMÉ BARTOLOMÉ (Cuadernos Dieciochistas)
Wine trade in the province of León in the Eighteenth Century: types and problems. Study of the types of the wine sales in the province of León in the Eighteenth Century, focusing on the importance of wine producers, «wine producers’ guilds» and how they controlled this trade, especially retail sales. The study also includes other kinds of wine trade organized with forced suppliers such as those in the of Astorga and its surroundings. We have also analyzed the conflicts which happened between the producers and the local authorities, caused by the retail sale which were more frecuent in the cities of Ponferrada and León.